Tingkat Depresi di Kalangan Pelajar: Implikasi Peran Gender dan Aliran Akademik - Sulaiman, Noor Azimah (Jurnal Bimbingan dan Konseling Pandohop, 2025)
This study aims to analyze the factors influencing the level of depression among students, focusing on the impact of gender and academic stream. A total of 291 final-year students from two Sixth Form Centers in Brunei Darussalam participated in this study. Data were collected using the Depression, Anxiety, and Stress Scale 21 items (DASS21), which measures depression levels across five categories: normal, mild, moderate, severe, and very severe. The results showed that the majority of students (52%) were in the normal depression category, while 16% experienced mild depression and 17% experienced moderate depression. Analysis based on gender revealed that female students tended to have higher depression levels compared to male students. Additionally, students from the arts stream showed higher levels of depression compared to those from the science stream, with 56% of arts students falling into the mild to very severe depression categories, compared to only 39% of science students. This study concludes that both gender and academic stream play an important role in determining students' depression levels, with female students and those in the arts stream being more vulnerable to pressures that affect their mental well-being. These findings provide valuable insights for designing more specific psychosocial interventions, such as stress management programs and group counseling, particularly for students in the arts stream.